2017
DOI: 10.3892/mmr.2017.8026
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid inhibits spinal cord injury and inflammation through suppressing the p38 and Akt signaling pathways

Abstract: Gamboge is the dry resin secreted by Garcinia hanburyi Hook.f, with the function of promoting blood circulation, detoxification, hemostasis and killing insects, used for the treatment of cancer, brain edema and other diseases. Gambogic acid is the main effective constituent of Gamboge. The present study investigated the protective effects of gambogic acid on spinal cord injury (SCI) and its anti‑inflammatory mechanism in an SCI model in vivo. Basso, Beattie and Bresnahan (BBB) testing was used to detect the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…SCI is a serious disease that eventually results in loss of movement and sensation below the lesion (15,22). After SCI occurs, the inflammatory response has an important role in the pathogenesis of the injured spinal cord (23,24). The present study demonstrated that BMSC transplantation suppressed the expression of TLR4 and NF-κB in the injured spinal cord after trauma.…”
Section: Discussionsupporting
confidence: 53%
“…SCI is a serious disease that eventually results in loss of movement and sensation below the lesion (15,22). After SCI occurs, the inflammatory response has an important role in the pathogenesis of the injured spinal cord (23,24). The present study demonstrated that BMSC transplantation suppressed the expression of TLR4 and NF-κB in the injured spinal cord after trauma.…”
Section: Discussionsupporting
confidence: 53%
“…Although MSCs were reported to potentially lower angiogenesis [ 105 ], the surprisingly high expression of the VEGFA in LMSC−P3 ( Figure 7 ) is questionable due to the fact that elevated vasculature over the surface of cornea can potentially affect the visual acuity [ 106 , 107 ]. However, the elevated levels of VEGFA (growth factor-induced or transfected or topically applied) in the wound bed were reported to enhance the wound repair of dermis/skin [ 108 , 109 , 110 , 111 ], but not many studies on corneal surface were reported. These elevated levels of VEGFA also contradict decreased expression of MMP9, the factors reported to feedback regulation mechanism [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oleanolic acid can inhibit in ammation by blocking the p38 and JNK MAPK signaling pathways to promote the recovery of the injured spinal cord (Wang et al 2020). Other studies have shown that in ammation and astrocytes proliferation/activation after SCI are related to the p38 MAPK and Akt signaling pathways (Qiao Fu et al 2018;Wang et al 2017). The most important nding of this study is that X-ray irradiation acts as an inhibitor of the p38 MAPK and Akt signaling pathways, which can inhibit in ammation and the formation of the glial scar.…”
Section: Discussionmentioning
confidence: 99%